Conflitos sociais pelo acesso aos recursos: o extrativismo da mangaba (Hancornia speciosa Gomes) no povoado Pontal/Sergipe - ROCHA, Maria Margarette Lisboa (Universidade Federal do Pará, 2021)
Conflicts over access to resources for the practice of extractivism of mangaba in Sergipe are the object of analysis in this study. The survey was conducted through a case study in Pontal Village, in Indiaroba municipality in the state of Sergipe. The main procedures were observations, interviews and participation in the mobilization activities of gatherers. The findings show that among the various actors involved in the conflicts there are the women gatherers, self-styled 'mangaba gatherers ', threatened with losing access to the plants, which engage in the extraction of which depend on to survive. We found different types of conflicts that involve the mangaba gatherers, home owners and caretakers, as well as conflicts even among gatherers themselves. The dispute and competition are strong elements experienced by these women gatherers, in defending their rights, access to natural resources (mangabeiras where they collect fruits and mangroves where they collect shellfish), and also in defense of biodiversity conservation which is so important to the survival of man in harmony with nature.